Ontologi, Epistimologi, dan Aksiologi dalam Perspektif Filsafat Ilmu Dakwah di Era Komunikasi Digital - karisna, Nila Noer (Jisab, 2022)
Ontology, Epistemology, and Axiology in the Philosophical Perspective of Da'wah in the Age of Digital Communication. The development of the era of globalization is forcing people to be technology literate. Coupled with the Covid-19 pandemic, forcing people to carry out digital communication for daily needs, including spiritual needs. This is what underlies the da'i to be able to transform da'wah into the digital realm. But before that, it is necessary for the da'i to explore the philosophy of da'wah in order to create valuable content in communicating in the digital realm. This paper aims to find out more deeply about ontology epistemology and axiology in order to better know the benefits of da'wah. This paper uses a qualitative approach with a literature study method (library review), namely the technique of collecting writings, readings and other literature, both physical and digital specifically, and then analyzing the content of the study based on the focus of the problems discussed. The results showed 1) ontology in the form of the essence of the existence of da'wah in communication between da'i and mad'u. 2) epistemology in Islamic da'wah, namely bayani epistemology, in the form of sources used in preaching on social media, irfani epistemology, in the form of intuition from da'i and burhani epistemology, in the form of intellectual activity. 3) In understanding axiology, the preacher must first master his knowledge. While mad'u must be selective in choosing their da'i, Da'i and mad'u both must realize that digital users are very diverse. When the da'i does da'wah, he must be ready to face all kinds of mad'u. for that it is necessary to create a dialogue space in digital.